A Clinical Case Report of a Potential Acute Allergic Reaction with Titanium Dental Implant - Ali Robaian Alqahtani; Khalid Gufran; Fred Silva; Mateus Garcia Rocha; Jia Chang (Hindawi Limited, 2021)
Titanium hypersensitivity is rare, but it may exist among patients who need dental implant treatment. It could contribute to mild or severe peri-implant tissue hypersensitivity reactions and affect patients' oral and general health according to some clinical reports. In extreme cases, it may lead to implant failure or extraction. In this case report, a 64-year-old Caucasian female patient received a titanium implant placement on #5. Right after the implant placement, she reported the symptoms of pain, eczema, and slight extraoral swelling, along with significant burning sensation occurring intra- and extraorally. The symptoms were not released after the systemic intervention of antibiotics for six days. On retrieving her medical history, the patient reported a previous allergic reaction to jewelry-like earrings in her childhood. The diagnosis of titanium hypersensitivity was made based on the rapid onset of symptoms and her metal allergy history. Therefore, the dental implant was removed after diagnosis, and a bone allograft was used to preserve the alveolar bone volume. Immediately after implant extraction, the swelling and burning sensation were receded. A complete recovery was achieved three weeks later. The dimension of the alveolar ridge bone was found well maintained in 10 weeks follow-up visit. Conclusion. Rapid onset of peri-implant gingival swelling may indicate a hypersensitivity to titanium implant in the clinic. For patients with a history of allergy to jewelry, the hypersensitivity tests to titanium alloy such as patch test or lymphocyte transformation test should be recommended as part of the dental implant treatment plan.